Domestic water carrying and its implications for health: a review and mixed methods pilot study in Limpopo Province, South Africa - Geere Jo-Anne L; Hunter Paul R; Jagals Paul (BMC, 2010)
Abstract Background Lack of access to safe water remains a significant risk factor for poor health in developing countries. There has been little research into the health effects of frequently carrying containers of water. The aims of this study were to better understand how domestic water carrying is performed, identify potential health risk factors and gain insight into the possible health effects of the task. Methods Mixed methods of data collection from six were used to explore water carrying performed by people in six rural villages of Limpopo Province, South Africa. Data was collected through semi-structured interviews and through observation and measurement. Linear regression modelling were used to identify significant correlations between potential risk factors and rating of perceived exertion (RPE) or self reported pain. Independent t-tests were used to compare the mean values of potential risk factors and RPE between sub-groups reporting pain and those not reporting pain. Results Water carrying was mainly performed by women or children carrying containers on their head (mean container weight 19.5 kg) over a mean distance of 337 m. The prevalence of spinal (neck or back) pain was 69% and back pain was 38%. Of participants who carried water by head loading, the distance walked by those who reported spinal pain was significantly less than those who did not (173 m 95%CI 2-343; p = 0.048). For head loaders reporting head or neck pain compared to those who did not, the differences in weight of water carried (4.6 kg 95%CI -9.7-0.5; p = 0.069) and RPE (2.5 95%CI -5.1-0.1; p = 0.051) were borderline statistically significant. For head loaders, RPE was significantly correlated with container weight (r = 0.52; p = 0.011) and incline (r = 0.459; p = 0.018) Conclusions Typical water carrying methods impose physical loading with potential to produce musculoskeletal disorders and related disability. This exploratory study is limited by a small sample size and future research should aim to better understand the type and strength of association between water carrying and health, particularly musculoskeletal disorders. However, these preliminary findings suggest that efforts should be directed toward eliminating the need for water carrying, or where it must continue, identifying and reducing risk factors for musculoskeletal disorders and physical injury.